2022
DOI: 10.3390/coatings12101491
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Investigation and Cyclic Oxidation Resistance of Ce-Si-Modified Aluminide Coating Deposited by Pack Cementation on Inconel 738LC

Abstract: The synergistic effect of Si and Ce addition on the oxidation resistance of a pack cementation aluminide coating applied on a Ni-based IN738LC superalloy substrate was investigated in this study. The structural and thermal influences of both Si and Ce, focusing on morphology, oxidation behavior, and scale spallation tendency, are accordingly discussed based on the experimental results using X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy-dispersive X-ray analyses (EDX). For this purpose… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…Furthermore, it was also characterized by an extended service life. It was stressed that while specimens after simple aluminide lost their scale, the Si-modified aluminide coatings retained their protective capabilities even after 300 h. Such behavior was also reported for Inconel 738LC protected with a Ce-Si-modified NiAl coating obtained by using PC [11]. It was found that the simultaneous addition of 1% cerium and 6% silicon led to the formation of Ce 1 Si 6 , which limits the oxygen diffusion, promotes the growth of the continuous Al 2 O 3 layer, and further enhances the hot-oxidation resistance of the coating.…”
Section: Pack Cementation (Pc) and Above The Pack/vapor-phase Alumini...supporting
confidence: 56%
See 1 more Smart Citation
“…Furthermore, it was also characterized by an extended service life. It was stressed that while specimens after simple aluminide lost their scale, the Si-modified aluminide coatings retained their protective capabilities even after 300 h. Such behavior was also reported for Inconel 738LC protected with a Ce-Si-modified NiAl coating obtained by using PC [11]. It was found that the simultaneous addition of 1% cerium and 6% silicon led to the formation of Ce 1 Si 6 , which limits the oxygen diffusion, promotes the growth of the continuous Al 2 O 3 layer, and further enhances the hot-oxidation resistance of the coating.…”
Section: Pack Cementation (Pc) and Above The Pack/vapor-phase Alumini...supporting
confidence: 56%
“…Interestingly, the most frequently modified nickel-based alloys are those with the highest oxidation resistance, possessing high mechanical strength. These involve Rene 80 [8,18,63], Inconel 625 [13,57,58], Inconel 713 [39,40,52], Inconel 718 [41], Inconel 738L [11,19,22,36,45,59,61,65,68] and CMSX-4 [17,30,42,44,46]. One should highlight that the research involving conventional nickel-based superalloys is mainly dedicated to future high-temperature applications.…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…Numerous studies have been conducted to form carbide precipitates to improve the mechanical properties of cobalt, nickel, or iron superalloys [4,5,[7][8][9]. While some of these studies aimed to form regional carbides throughout the alloy's microstructure [4,5,[7][8][9], others focused on forming aluminide nitride, boride, carbide, etc., on the surface of these alloys [10][11][12][13]. These advanced surface coatings often offer a more cost-effective approach to increasing service life.…”
Section: Introductionmentioning
confidence: 99%
“…However, cobalt-based superalloys have many applications in high-temperature abrasive environments such as gas turbines, nuclear power plants, high-temperature furnaces, and the oil and gas industry [1,2,22]. When thermomechanical coatings are applied to the surfaces of these superalloys, they improve surface hardness and chemical inertness and provide a thermal barrier effect, resulting in enhanced oxidation, corrosion, and wear resistance at high temperatures [10][11][12][13][14][17][18][19][20][21]. These advantages enhance the performance of cobalt-based superalloys, enabling their use in more challenging operating conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation